Intellectual Disability and Bioethics. Responsible Educational Needs (Revista Iberoamericana de Bioética, 2021)
Disability and bioethics is a joint reflection that seeks to focus on the human factor and how the development of the human condition is a determining factor in the life of a person with intellectual disability. It understands that many of the factors that directly affect disability are a response to current social values and their systemic organisation around results, forgetting the individual and their processes. From this point of view, bioethics becomes a new social paradigm where the focus is on the person and of course, on the development of his/her human condition.
Keywords: bioethics; intellectual disability; human condition; responsibility; society